The impact of organizational culture on a firm's capability to innovate the business model. (3rd August 2015) - Hock, Marianne; Clauss, Thomas; Schulz, Esther
Abstract : Recent literature on business model innovation tries to identify operational changes occurring within the business model components. We suggest that a significant part of the business model cannot be understood without an investigation of the underlying logic of the firm. Drawing on organizational culture literature, this study explores the idea that parts of the capabilities that enable business model innovation are determined by the firm's underlying cultural values. In this study, we utilize existing literature on organizational culture to analyze the underlying organizational values of the two main business model design themes (novelty and efficiency) and link these to the firm's capabilities that foster business model innovation. By empirically analyzing a sample of 305 companies in the engineering industry, we find that novelty‐oriented cultural values foster capabilities (strategic sensitivity, collective commitment and resource fluidity) in favor of business model innovation, while efficiency‐oriented cultural values do not show positive effects. We further find that strategic sensitivity and resource fluidity significantly enhance the propensity to business model innovation.